1637. Improving Transitions of Care in the Division of Infectious Diseases. (26th November 2018) - Paim, Ana; Vijayvargiya, Prakhar; Garrigos, Zerelda Esquer; Tan, Eugene; O'Horo, John
Abstract: Background: Patients dismissed from the hospital on oral or intravenous antibiotics frequently need follow-up appointments with the Division of Infectious Diseases (ID). Follow-up appointments may be inappropriately scheduled with respect to timing and indication. Suboptimal transitions of care may lead to increased no-shows and ultimately poor patient outcomes. Methods: The baseline sample included 102 patients seen by the inpatient ID services at Mayo Clinic's Rochester Methodist and Saint Mary's Hospitals between January 1, 2017 and June 30, 2017. Defects in transitions of care were categorized as those pertaining to sign-off templates, sign-off labels, follow-up priority, and timing. The current transfer of care system from our institution is outlined in Figure 1. Results: Out of 102 patients, 75 (74%) had at least one defect identified. Root cause analysis revealed multiple factors contributing to this performance gap (Figure 2). Patients often have variable health literacy and social or financial difficulties. There are often multiple ID providers with inadequate time to properly orchestrate follow-up. There are undefined checkpoints and triaging in the department's scheduling policies. Interventions involved reformatting the ID sign-off template and clarifying the roles of providers in the transitions-of-care process. Analysis after 6 months of implementation revealed improvement of communication among teams, decline in improper sign off by 13% and decrease in antibiotic prescription errors by 2%. Conclusion: This study demonstrates that well-designed sign-off templates can help with effective communication of the final treatment plan among providers and possibly improve patient outcomes. The target goal is to reduce the number of improper sign-offs by 50% within 1 year. Disclosures: All authors: No reported disclosures.